Bacterial Meningitis Associated with Pituitary Macroadenoma: Systematic Review - TOUDOU DAOUDA Moussa; ASSADECK Hamid; HASSANE DJIBO Fatimata (Journal of Neurological Research And Therapy, 2017)
Introduction Bacterial meningitis complicates rarely pituitary macroadenomas. The aim of our systematic review is to study the features of the association between bacterial meningitis and pituitary macroadenoma. Methods We conducted a literature search in both MedLine and Google Scholar database from 1967 to October 2016 and reviewed all cases described of the association between bacterial meningitis and pituitary macroadenoma apart from any surgical act and without pituitary apoplexy. Results We found 14 articles describing 16 patients aged of 22-69 years old with a male predominance (sex ratio 4.3). Two patients (12.5%) had a well-documented clinical history of pituitary macroadenoma prior to the diagnosis of bacterial meningitis. Rhinorrhea has been found as the most common symptom through six patients (37.5%). Through the CSF culture, bacterial meningitis among patients suffering of pituitary macroadenoma commonly was due to Streptococcus pneumoniae. The examination in 18.75% of cases revealed signs related to pituitary macroadenoma (ophthalmoplegia and blindness). Six patients (37.5%) had received a treatment by dopaminergic agonist alone and 4 patients (25%) were treated with dopaminergic agonist associated with surgical treatment. Surgical treatment consisted of closure of the osteomeningeal breach in 12.5% (2/16) and tumor resection in 31.25% (5/16). Three patients (18.75%) had benefited tumor resection without prior agonist treatment. The mortality was 12.5% (2/16). Conclusion Our systematic review shows that bacterial meningitis represents a rare initial symptom leading to the diagnosis of invasive pituitary macroadenoma.
Keywords: pituitary macroadenoma